Comparative Analysis of Volatile Defensive Secretions of Three Species of Pyrrhocoridae (Insecta: Heteroptera) by Gas Chromatography-Mass Spectrometric Method - Krajicek, Jan; Havlikova, Martina; Bursova, Miroslava; Ston, Martin; Cabala, Radomir; Exnerova, Alice; Stys, Pavel; Bosakova, Zuzana (PLoS One, 2016)
The true bugs (Hemiptera: Heteroptera) have evolved a system of well-developed scent glands that produce diverse and frequently strongly odorous compounds that act mainly as chemical protection against predators. A new method of non-lethal sampling with subsequent separation using gas chromatography with mass spectrometric detection was proposed for analysis of these volatile defensive secretions. Separation was performed on Rtx-200 column containing fluorinated polysiloxane stationary phase. Various mechanical irritation methods (ultrasonics, shaking, pressing bugs with plunger of syringe) were tested for secretion sampling with a special focus on non-lethal irritation. The preconcentration step was performed by sorption on solid phase microextraction (SPME) fibers with different polarity. For optimization of sampling procedure, Pyrrhocoris apterus was selected. The entire multi-parameter optimization procedure of secretion sampling was performed using response surface methodology. The irritation of bugs by pressing them with a plunger of syringe was shown to be the most suitable. The developed method was applied to analysis of secretions produced by adult males and females of Pyrrhocoris apterus, Pyrrhocoris tibialis and Scantius aegyptius (all Heteroptera: Pyrrhocoridae). The chemical composition of secretion, particularly that of alcohols, aldehydes and esters, is species-specific in all three pyrrhocorid species studied. The sexual dimorphism in occurrence of particular compounds is largely limited to alcohols and suggests their epigamic intraspecific function. The phenetic overall similarities in composition of secretion do not reflect either relationship of species or similarities in antipredatory color pattern. The similarities of secretions may be linked with antipredatory strategies. The proposed method requires only a few individuals which remain alive after the procedure. Thus secretions of a number of species including even the rare ones can be analyzed and broadly conceived comparative studies can be carried out.
Keywords: Animals; Gas Chromatography-Mass Spectrometry; Female; mužské pohlaví; zvířata; těkavé organické sloučeniny; Male; Volatile Organic Compounds; plynová chromatografie s hmotnostně spektrometrickou detekcí; ženské pohlaví; Heteroptera